Pengaruh Dukungan Logistik Terpadu di Wilayah Natuna terhadap Kesiapan Operasi KOGABWILHAN I - Andi Mawanto (Jurnal Logistik Indonesia, 2020)
This study aims to test whether the anchoring facilities and provisioning support in the Natuna region are the operational readiness of Kogabwilhan I. The sample in this study were 55 respondents. This type of research is quantitative using Statistical Products and Service Solutions 25 (SPSS 25). The independent variable in this study is the ability of the anchoring facility and provisioning support, while the dependent variable is the operational readiness of Kogabwilhan I. The results show that the ability of the anchoring facility and provisioning support affects the operational readiness of Kogabwilhan I. This can be seen from the test results that show the variable capability. The anchoring facility (X₁) has a t value of 2,565> t table value at a significance level of 0.05 of 0.200665 with sig (0.013) t value table at a significance level of 0.05 of 0.200665 with sig 0.000